2015
DOI: 10.1016/j.febslet.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

How is the inner circadian clock controlled by interactive clock proteins?

Abstract: Edited by Wilhelm JustKeywords: Circadian rhythm 3D crystal structure Drosophila and mammalian clock protein Circadian clock mechanism a b s t r a c t Most internationally travelled researchers will have encountered jetlag. If not, working odd hours makes most of us feel somehow dysfunctional. How can all this be linked to circadian rhythms and circadian clocks? In this review, we define circadian clocks, their composition and underlying molecular mechanisms. We describe and discuss recent crystal structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 152 publications
(328 reference statements)
0
32
0
Order By: Relevance
“…Another group determined the crystal structure of CRY2-PER2 complex [37] and showed that the relevant cysteine in CRY2 [38] also functions as an intermolecular zinc-binding site [37]. Details of the structure of CRYs based on recent structural analyses are discussed in a review [39]. …”
Section: Structural-biological Analyses Of Crysmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group determined the crystal structure of CRY2-PER2 complex [37] and showed that the relevant cysteine in CRY2 [38] also functions as an intermolecular zinc-binding site [37]. Details of the structure of CRYs based on recent structural analyses are discussed in a review [39]. …”
Section: Structural-biological Analyses Of Crysmentioning
confidence: 99%
“…Moreover, deregulation of signalling cascades, such as Hedgehog -, Notch -, and Wnt -signalling pathways, might cause the development of the unusual ductal structures in Tg mice. C414A CRY1 might affect mouse Timeless (TIM; TIM is known as a CRY-binding protein [39]) and might perturb the function of TIM in the pancreas, possibly leading to aberrant activation of the signalling pathways, as described in one report [67]. Actually, some constituents of Hedgehog -signalling and Wnt -signalling pathways were elevated in the Tg mice islet [52].…”
Section: Unusual Ductal Structures In the Pancreasmentioning
confidence: 99%
“…CRYs form a complex with PERs and are involved in transcriptional repression of the ARNTL (BMAL1)/CLOCK heterodimers (Figure 3) [2]. The SNPs or deregulation of CRY1 and/or 2 are associated with increased susceptibility and mortality to several type of cancer [39].…”
Section: Resultsmentioning
confidence: 99%
“…ARNTL (BMAL1)–CLOCK/NPAS2 heterodimers also induce a secondary regulatory loop which activates the transcription of retinoic acid-related orphan nuclear receptors, NR1D1, NR1D2 , RORA and RORB . RORA activates the transcription of ARNTL (BMAL), whereas NR1D1/D2 represses it [2] (see Figure 3 for a schematic description of the circadian clock mechanism in mammals). TIMELESS, a member of an evolutionary conserved family of ortologs [93, 94], is involved not only in circadian rhythmicity, interacting directly with CRY1 [95], but also in embryonic development, cell cycle progression, DNA replication, and the DNA damage response [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation